The dimensions of environmental performance: a systematic review for a common yardstick / Sarah Ferehoun, Fadoua Laghzaoui and Mostafa Abakouy - Ferehoun, Sarah; Laghzaoui, Fadoua; Abakouy, Mostafa (UiTM Press, 2024)
Many studies conducted during the last decade have suggested environmental performance benefits. However, not many studies have attempted to synthesize these studies and present a broader picture of the conceptualization of this performance. Therefore, this study aimed to systematically analyze environmental performance dimensions and propose a conceptual framework based on the prior literature. The PRISMA statement was used as a guideline for this systematic reviews, structuring data collection, and identifying research gaps from studies over the period 19902022. The analysis included 36 papers from the Web of Science and Scopus databases. Four dimensions of environmental performance were identified: managerial, operational, based on outcomes, and according to the global context. The analysis identified 129 codes grouped into the four dimensions. However, the study results varied because of the multidimensionality of the concept and the context in which the organizations operate. The findings convey key insights into the current state of scholarly investigation on environmental performance. The results also showed multiplicity in the choice of indicators and environmental performance variables (inputs, outputs, stakeholder relations, impacts, eco-innovations). Research directions were suggested to improve the understanding of the conceptualization of environmental performance, recommend a unified model, and advance future research in this increasingly important and expansive area.